Introducing a sector-wide pooled fund in a fragile context: mixed-methods evaluation of the health transition fund in Zimbabwe. Issue 6 (4th June 2019) - D'Aquino, Luigi; Pyone, Thidar; Nigussie, Assaye; Salama, Peter; Gwinji, Gerald; van den Broek, Nynke
Abstract : Introduction: Aid effectiveness and improving its impact is a central policy matter for donors and international organisations. Pooled funding is a mechanism, whereby donors provide financial contributions towards a common set of broad objectives by channelling finance through one instrument. The results of pooled funds as an aid mechanism are mixed, and there is limited data on both methodology for, and results of, assessment of effectiveness of pooled funding. Methods: This study adapted a conceptual framework incorporating the Paris Principles of Aid Effectiveness and qualitative methods to assess the performance of the Health Transition Fund (HTF) Zimbabwe. 30 key informant interviews, and 20 focus group discussions were conducted with informants drawn from village to national level. Descriptive secondary data analysis of Demographic Health Surveys, Health Management Information Systems (HMIS) and policy reports complemented the study. Results: The HTF combined the most optimal option to channel external aid to the health sector in Zimbabwe during a period of socioeconomic and political crisis. It produced results quickly and at scale and enhanced coordination and ownership at the national and subnational level. Flexibility in using the funds was a strong feature of the HTF. However, the initiative compromised on the investment in local capacity and systems, since the primary focus was on restoring essential services within a nearly collapsed healthcare system, rather than building long-term capacity. Significant changes in maternal and newborn health outcomes were observed during the HTF implementation in Zimbabwe. Conclusion: A framework which can be used to assess pooled funds was adapted and applied. Future assessments could use this or another framework to provide new evidence regarding effectiveness of pool donor funds although the frameworks should be properly tested and adapted in different contexts.